Video-Based Performance Analysis of West Java Artistic Swimming - Maharani Sekar Langit; Dede Rohmat Nurjaya; Gafur Ammar Santoso; Tian Kurniawan (Journal of Physical Education Health and Sport, 2025)
The purpose of this study was to analyze the performance of artistic swimmers from West Java using video as a more objective evaluation tool. Athlete performance has usually been assessed directly, which can lead to subjectivity. Kinematic analysis was used for data from three female athletes from qualifying round of the 2025 West Java Provincial Sports Week and the 2025 West Java Regional Sports Championship . Leg height index (LHI) and average leg angle deviation (LAD) in vertical and knight movements were calculated using Kinovea software for frame-by-frame data extraction. The LAD was calculated based on the angle deviation from the ideal position, and the LHI values were compared to the FINA standard height card. The analysis results show that there are quite noticeable technical differences between the subjects.  SSK a showed the best and most consistent performance, with an average LHI of 9.5 (Vertical) and 9.6 (Knight) that was closer to the FINA standard, and her LAD was also relatively small on both elements. AEN demonstrated a stable LHI (9.1 Vertical; 9.2 Knight). Compared to other athletes, AEN LAD values tended to be higher, which may indicate that she reached sufficient height to make utilizing the angles around her peak more difficult. Meanwhile, LNL achieved a lower LHI (9.1 Vertical; 8.9 Knight) as well as the smallest LAD value in the Knight movement (1.3°). Although her vertical LAD (5.9°) was higher than AEN. The results indicate that video-based performance analysis can be successfully applied to the evaluation of artistic swimming performance.